Aktualisasi Program Tahfidzul Qur’an Pada Sekolah Luar Biasa - Rizka Harfiani (Al-Ulum: Jurnal Pendidikan Islam, 2021)
The lack of special schools based on Islam and the Qur'an is one of the factors causing children with special needs to not get access to Islamic religious education. This study aims to analyze the actualization of the Tahfidzul Qur'an program at the integrated Islamic special school "Sahabat Al-Qur'an" located in Binjai City. This study uses a qualitative approach, with the type of field research. Data collection techniques are through observation, interviews, and documentation, which are then analyzed using an interactive analysis model, and test the validity of the data using the triangulation method. The implication of the results of this study is to provide an overview of the implementation of the Tahfidzul Qur'an program for children with special needs in special schools, so that they can carry out their religious obligations as Muslims as well as normal children.Keywords: Program, Tahfidzul Qur'an, Extraordinary School